Leelawati aur Chandrawati ka Qissa (1868): Introduction, Analysis and Editing - Sumaira Umar (بازیافت)
<span style="font-size: 12.0pt; line-height: 107%; font-family: "Times New Roman",serif; mso-ascii-theme-font: major-bidi; mso-fareast-font-family: "Times New Roman"; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-font-kerning: 1.0pt; mso-ansi-language: #007F; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">During the 19th century in India, women were often restricted from pursuing education beyond basic literacy and domestic skills. The prevalent belief was that a woman's primary role was to take care of the household and raise children, and therefore higher education for women was seen as unnecessary. However, there were individuals and organizations who recognized the importance of educating women and advocated for their right to receive a formal education. One of the key figures in the promotion of women's education during this time was social reformer Raja Ram Mohan Roy, who believed that educating women was essential for the progress of society. Despite these efforts, the curriculum for women's education during the 19th century was primarily focused on practical skills such as sewing, cooking, and childcare, rather than providing a well-rounded education. However, there were attempts to introduce subjects like literature, science, and social studies into the curriculum for girls, albeit on a limited scale. The status of women's education in 19th century India was marked by significant challenges and limitations. While there were efforts to promote female education by notable individuals and organizations, the prevailing societal norms and restrictions hindered the progress of women's education during this time. It was not until much later that significant strides were made in improving women's access to education and expanding the scope of their studies. By chosing a qissa of ninteenth century my aim here is to introduce the efforts by local scribes in female education. The story genre was used to pursuade females in didactic works. The qissa at hand “Leela wati o Chandrawati ka Qissa” was published from government press and in a short time its 2nd edition went out, which shows its populartiy.